PELATIHAN PENGEMBANGAN EKONOMI KREATIF BAGI PEKERJA MIGRAN INDONESIA DI MALAYSIA - Ibrahim Ibrahim; Inka Nusamuda Pratama; Ilham Zitri (Smart Education, 2024)
Abstarct : The Creative Economy Development Training for Indonesian Migrant Workers in Malaysia addresses participants' lack of understanding and skills in marketing strategies and developing creative ideas essential for inclusive economic growth. Group discussions, simulations, and practical sessions are at the heart of this training, allowing participants to share experiences, develop thinking, and apply learned concepts in authentic contexts. Apart from improving individual skills, the main aim of the training is to strengthen awareness of the vital role of the creative economy in driving inclusive growth. The results of this program were that most participants needed more knowledge in marketing and developing creative ideas. Therefore, an interactive and participatory approach was used in preparing activities. Participants develop a deep understanding of effective marketing strategies and creative idea development techniques. At the end of the program, participants will not only be able to become active agents of change in advancing the creative economy in Malaysia. Still, they can also improve the welfare of the Indonesian migrant worker community. This training not only functions as a source of knowledge but also as a forum for building sustainable capacity and awareness in the context of the creative economy. Keywords : Training; Creative Economy; Indonesian Migrant Workers; Malaysia Abstrak : Pelatihan Pengembangan Ekonomi Kreatif bagi Pekerja Migran Indonesia di Malaysia dirancang untuk mengatasi kekurangan pemahaman dan keterampilan peserta dalam strategi pemasaran dan pengembangan ide kreatif yang esensial bagi pertumbuhan ekonomi inklusif. Diskusi kelompok, simulasi, dan sesi praktis menjadi inti dari pelatihan ini, memungkinkan peserta untuk berbagi pengalaman, mengembangkan pemikiran, dan menerapkan konsep yang dipelajari dalam konteks nyata. Selain meningkatkan keterampilan individu, tujuan utama pelatihan adalah memperkuat kesadaran akan peran vital ekonomi kreatif dalam menggerakkan pertumbuhan yang inklusif.metode yang digunakan dalam kegiatan ini yaitu ceramah dan diskusi. Hasil program ini yaitu, mayoritas peserta teridentifikasi belum memiliki pengetahuan yang memadai dalam pemasaran dan pengembangan ide kreatif, oleh karena itu pendekatan interaktif dan partisipatif digunakan dalam penyusunan kegiatan. Peserta mengembangkan pemahaman yang mendalam tentang strategi pemasaran yang efektif dan teknik pengembangan ide kreatif. Diakhir program, peserta tidak hanya mampu menjadi agen perubahan aktif dalam memajukan ekonomi kreatif di Malaysia, tetapi juga dapat meningkatkan kesejahteraan komunitas pekerja migran Indonesia secara keseluruhan. Pelatihan ini bukan hanya berfungsi sebagai sumber pengetahuan, tetapi juga sebagai wadah untuk membangun kapasitas dan kesadaran yang berkelanjutan dalam konteks ekonomi kreatif. Kata Kunci : Pelatihan; Ekonomi Kreatif; Pekerja Migran Indonesia; Malaysia